Serial Picture Media Improves Expressive Language Skills and Religious and Moral Values of 4-5 Year Old Children - Nurhayati Tine; Sulastya Ningsih; Sri Wahyuni S. Pongoliu (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
The development of language skills of children aged 4-5 years is still not optimal. This is indicated by children having difficulty expressing ideas, constructing sentences, and using simple language. Based on this, this study aims to analyze the effect of serial images on expressive language skills and instilling values in early childhood ages 4-5 years. The type of research the researcher conducts is quantitative research with a quasi-experimental approach or Quasi-experimental Design. The population of this study was all children in class B aged 4-5 years, totalling 50 people. The sampling technique in this study used purposive sampling of 20 people, and each class was divided into two groups. Data collection techniques include observation techniques, tests, and documentation of learning outcomes. The instrument used to collect data is a questionnaire sheet. The research data analysis technique uses inferential statistical analysis. The study results are as follows. First, there is a relationship between serial images and the expressive language skills of early childhood. Second, there is a relationship between expressive language skills and religious and moral values. Third, there is a relationship between serial images and children's ability to draw series and instil religious and ethical values. It is concluded that serial photos can improve children's ability to draw series and instil religious and moral values.